Pengaruh Kompleksitas Operasi, Reputasi KAP, Ukuran Perusahaan dan Audit Tenure terhadap Audit Delay - Ferry Diyanti; Muhamad Ariansyah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this study is to examine the influence of operational complexity, reputation of the public accounting firm, company size, and audit tenure on audit delay. The population in this study comes from companies in the property and real estate sectors listed on the Indonesia Stock Exchange in 2020-2023. The sample was determined using the purposive sampling method and was obtained by 65 companies. The analysis tool used to process the data is multiple linear regression analysis. This study provides results that the operation complexity and reputation of the public accounting firm have no effect on audit delay. Company Size has a negative effect on audit delay. Audit tenure has a negative effect on audit delay.